Experimental Study of Physical Properties of Laminated Veneer Lumber Made by Three Cameroonian Hardwoods with Two Adhesives - Celestin Patrick Tankou Ntahayo; Jeanne Sandrine Mabekou Takam; Hervice Kouefouet; Emmanuel Foadieng; Rostand Moutou Pitti; Pierre Kisito Talla (Advances in Materials Science and Engineering)
This work deals with the determination of some properties of laminated veneer lumber (LVL) made from tropical hardwoods, specifically focusing on Cameroonian woods. The LVL samples are manufactured using veneer from three tropical wood species: Ayous, Ilomba, and Bete. Two types of adhesives are used: a neoprene contact adhesive (Magpow) and a white vinyl adhesive (Nemo). The specimens have undergone multiple drying cycles, and hundreds of samples from each species have been selected with dimensions of 1 cm × 1 cm × 1 cm. These samples are then machined according to the specific wood grain of each species. The experiments conducted aim to determine properties such as moisture content, densities, volume swelling, shrinkage coefficients, and the hygroscopic point of equilibrium of the samples. Swelling and shrinkage measurements allow for the visualization of sample dimensions in relation to humidity levels, and the hysteresis of the adsorption phenomenon of the LVL is also obtained. The results show that regardless of the type of adhesive or veneer used, LVLs are denser than the wood they are made from. For each type of LVL, the ratio between the mass of a sample saturated in water and the mass of the dried sample remains constant. The rule of mixture is investigated, and the density properties of materials and the vacuum rates of LVL samples are compared with experimental data.